Causality, Meaningful Complexity and Embodied Cognition - Carsetti, A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
With respect to the possible outlining of new models of the process of knowledge construction, we are really faced, at the moment, with the appearance of a new frontier: a frontier that appears strictly linked to the emergence of a conceptual revolution at the level of the analysis of that peculiar entanglement of complexity, information, causality, meaning, emergence, teleology and intentionality that characterizes the unfolding of the "natural forms" of human cognition. To recognize some of the peculiar knots of this particular conceptual revolution precisely constitutes the first target of the volume. Cognitive activity is rooted in Reality, but at the same time represents the necessary means whereby Reality can embody itself in an objective way: i.e., in accordance with an in-depth nesting process and a surface unfolding of operational meaning. In this sense, the objectivity of Reality is also proportionate to the autonomy reached by cognitive processes. Within this conceptual framework, reference procedures thus appear as related to the modalities providing the successful constitution of the channel, of the actual link, in particular, established at the neural level between operations of vision and thought. Such procedures ensure not a simple "regimentation" or an adequate replica, but, on the contrary, the real constitution of a cognitive autonomy in accordance with the truth. A method thus emerges which is simultaneously project, telos and regulating activity: a code that becomes process, positing itself as the foundation of a constantly renewed synthesis between function and meaning. In this sense, at the level of cultural evolution, reference procedures act as guide, mirror and canalisation with respect to primary information flows and involved selective forces. They also constitute a precise support for the operations which "imprison" meaning and "inscribe" the "file" considered as an autonomous categorial (and generating) system. In this way, they offer themselves as the actual instruments for the constant renewal of the code, for the invention and the actual articulation of an ever-new incompressibility.
Consciousness, Intentionality and Self-Organization -- The Link Between Brain Learning, Attention, and Consciousness -- Emergence of Intentional Procedures in Self-Organizing Neural Networks -- Action Goal Representation and Action Understanding in the Cerebral Cortex -- Truth, Randomness and Impredicativity -- The Genesis of Mathematical Objects, Following Weyl and Brouwer -- Randomness, Determinism and Programs in Turing$1 (Bs Test -- ?-Incompleteness, Truth, Intentionality -- Complexity, Incomputability and Emergence -- Leibniz, Complexity and Incompleteness -- Incomputability, Emergence and the Turing Universe -- Computational Models of Measurement and Hempel$1 (Bs Axiomatization -- Impredicativity of Continuum in Phenomenology and in Non-Cantorian Theories -- Epistemic Complexity and Causality -- Reasons Against Naturalizing Epistemic Reasons: Normativity, Objectivity, Non-computability -- Some Remarks on Causality and Invariance -- Epistemic Complexity from an Objective Bayesian Perspective -- Embodied Cognition and Knowledge Construction -- The Role of Creativity and Randomizers in Human Cognition and Problem Solving -- The Emergence of Mind: A Dualistic Understanding -- Doing Metaphysics with Robots -- Knowledge Construction, Non-Standard Semantics and the Genesis of the Mind$1 (Bs Eyes.s
Keywords: Philosophy (General).; Genetic epistemology; Philosophy of mind; Computer simulation; Philosophy; Epistemology; Statistical Physics, Dynamical Systems and Complexity; Simulation and Modeling; Philosophy of Mind